Out-of-Pocket and Informal Payment Before and After the Health Transformation Plan in Iran: Evidence from Hospitals Located in Kurdistan, Iran - Bakhtiar Piroozi; Arash Rashidian; Ghobad Moradi; Amirhossein Takian; Hooman Ghasri; Tayyeb Ghadimi (Kerman University of Medical Sciences, 2017)
Background One of the objectives of the health transformation plan (HTP) in Iran is to reduce out-of-pocket (OOP) payments for inpatient services and eradicate informal payments. The HTP has three phases: the first phase (launched in May 5, 2014) is focused on reducing OOP payments for inpatient services; the second phase (launched in May 22, 2014) is focused on primary healthcare (PHC) and the third phase utilizes an updated relative value units for health services (launched in September 29, 2014) and is focused on the elimination of informal payments. This aim of this study was to determine the OOP payments and the frequency of informal cash payments to physicians for inpatient services before and after the HTP in Kurdistan province, Iran. Methods This quasi-experimental study used multistage sampling method to select and evaluate 265 patients discharged from hospitals in Kurdistan province. The study covered 3 phases (before the HTP, after the first, and third phases of the HTP). Part of the data was collected using a hospital information system form and the rest were collected using a questionnaire. Data were analyzed using Fisher exact test, logistic regression, and independent samples ttest. Results The mean OOP payments before the HTP and after the first and third phases, respectively, were US$59.4, US$17.6, and US$14.3 in hospital affiliated to the Ministry of Health and Medical Education (MoHME), US$39.6, US$33.7, and US$13.7 in hospitals affiliated to Social Security Organization (SSO), and US$153.3, US$188.7, and US$66.4 in private hospitals. In hospitals affiliated to SSO and MoHME there was a significant difference between the mean OOP payments before the HTP and after the third phase (P < .05). The percentage of informal payments to physicians in hospitals affiliated to MoHME, SSO, and private sector, respectively, were 4.5%, 8.1%, and 12.5% before the HTP, and 0.0%, 7.1%, and 10.0% after the first phase. Contrary to the time before the HTP, no informal payment was reported after the third phase. Conclusion It seems that the implementation of the HTP has reduced the OOP payments for inpatient services and eradicated informal payments to physician in Kurdistan province.